Insight in the Chemistry of Laser-Activated Dental Bleaching - Roeland Jozef Gentil De Moor; Jeroen Verheyen; Andrii Diachuk; Peter Verheyen; Maarten August Meire; Peter Jozef De Coster; Filip Keulemans; Mieke De Bruyne; Laurence James Walsh (The Scientific World Journal)
The use of optical radiation for the activation of bleaching products has not yet been completely elucidated. Laser light is suggested to enhance the oxidizing effect of hydrogen peroxide. Different methods of enhancing hydrogen peroxide based bleaching are possible. They can be classified into six groups: alkaline pH environment, thermal enhancement and photothermal effect, photooxidation effect and direct photobleaching, photolysis effect and photodissociation, Fenton reaction and photocatalysis, and photodynamic effect.